2020
DOI: 10.1371/journal.pone.0241476
|View full text |Cite
|
Sign up to set email alerts
|

Circulating whole genome miRNA expression corresponds to progressive right ventricle enlargement and systolic dysfunction in adults with tetralogy of Fallot

Abstract: Introduction The adult congenital heart disease population with repaired tetralogy of Fallot (TOF) is subject to chronic volume and pressure loading leading to a 40% probability of right ventricular (RV) failure by the 3rd decade of life. We sought to identify a non-invasive signature of adverse RV remodeling using peripheral blood microRNA (miRNA) profiling to better understand the mechanisms of RV failure. Methods Demographic, clinical data, and blood samples were collected from adults with repaired TOF (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Moreover, they described that miR-29-5p was significantly higher in DCM compared with IHD. Weldy et al [ 45 ] reported that the high plasma levels of miR-28-3p, miR-433-3p, and miR-371b-3p are related to increased right ventricular size. Moscoso et al [ 75 ] described the prognostic value of miR-499a and miR-125b in response to cardiac resynchronization therapy: the patients who positively responded to therapy showed lower plasma levels of these miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they described that miR-29-5p was significantly higher in DCM compared with IHD. Weldy et al [ 45 ] reported that the high plasma levels of miR-28-3p, miR-433-3p, and miR-371b-3p are related to increased right ventricular size. Moscoso et al [ 75 ] described the prognostic value of miR-499a and miR-125b in response to cardiac resynchronization therapy: the patients who positively responded to therapy showed lower plasma levels of these miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…7 Circulating miRNA is of particular interest as potential biomarkers of fibrosis and hypertrophy. 814 Circulating proteins of ventricular stretch, cardiac remodeling, oxidative stress, and inflammation are showing promise in guiding heart failure therapy in adult ischemic heart disease. 15 There are emerging data on circulating biomarkers to understand the mechanisms of heart failure in children with congenital heart disease including metabolic profiling to identify ventricular remodeling in aortic valve abnormalities, 16 defects in amino acid metabolism in Fontan circulation implicating altered energy metabolism 17 and altered extracellular matrix (ECM) proteins in interstage infants with single ventricle heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…From the genetic perspective, the etiology of TOF is multifactorial. Despite successful surgical repair, many patients have chronic volume loading caused by pulmonary regurgitation (PR) that leading to a 40% probability of right ventricular (RV) failure by the 3 rd decade of life [1,2] . In addition, some patients developed RV failure before 30 years of age.…”
Section: Introductionmentioning
confidence: 99%